Emotional intelligence and public relations : EQ is the new IQ - Zhang, Weiwu (Routledge, 2026)
Emotional intelligence, often referred to as emotional quotient (EQ), has emerged as a critical soft skill in public relations (PR), proven essential for performance, leadership, and fostering collaborative organizational cultures. Despite its importance, EQ remains understudied in PR contexts. This groundbreaking volume presents the first comprehensive collection of cutting-edge research and theoretical and practical insights exploring the pivotal role of EQ across PR practice and education.Leading scholars contribute original research, theoretical frameworks, and case studies examining EQ in various settings. The book covers diverse topics including EQ's importance in PR roles, internal communication, listening and mindfulness, leadership, intercultural relations, work-life harmony, crisis communication, health communication, organizational listening, social capital, and diversity initiatives. Each chapter provides practical recommendations for implementing EQ principles in daily PR practice and future research directions.This essential resource serves multiple audiences: PR educators seeking to incorporate EQ into their curriculum, researchers exploring the intersection of EQ and communication, and practitioners looking to enhance their professional capabilities. Whether used as a supplementary text for PR theory courses, a foundation for professional development, or a required text for specialized EQ classes, this volume delivers valuable insights into why EQ truly is the new IQ in public relations.
Keywords: Emotional intelligence.; Public relations -- Psychological aspects.; Emotional intelligence; Empathy; Social skills; Cultural intelligence; Public relations; Strategic communication; Leadership; PR leadership; PR education; Internal communication; Health communication; Crisis communication; Intercultural public relations; elektronické knihy; electronic books